Pancreatoprotective effects of Geniotrigona thoracica stingless bee honey in streptozotocin-nicotinamide-induced male diabetic rats - Muhammad Shakir Abdul Aziz; Nelli Giribabu; Pasupuleti Visweswara Rao; Naguib Salleh (2017)
Stingless bee honey (SLBH) has been claimed to possess multiple health benefits. Its anti-diabetic properties are however unknown. In this study, ability of SLBH from Geniotrigona thoracica stingless bee species in ameliorating pancreatic damage and in maintaining metabolic profiles were investigated in diabetic condition.